Study on the layout strategy of diaphragms to enhance the energy absorption of thin-walled square tubes. (February 2021) - Xing, Jie; Xu, Ping; Yao, Shuguang; Zhao, Hui; Zhao, Ziliang; Wang, Zhangjun
Abstract: This study focuses on a thin-walled square tube with diaphragms (TSTD) as an energy-absorbing structure. To investigate the layout strategy of diaphragms to improve the crushing response of a TSTD, both experiments and finite element model (FEM) simulations are carried out under quasi-static loading. Based on the experimental and simulation results, the crushing behavior of one group of specimens with different diaphragm intervals is compared. Three deformation modes are observed, which include the symmetric mode, mixed mode, and extensional mode. The optimal diaphragm interval value is found at the critical point when the deformation mode transitions from the mixed mode to the extensional mode. Furthermore, parametric studies are performed on the deformation mode, the mean crushing force (MCF), and the specific energy absorption (SEA). The criterion that dominates the deformation mode is revealed, and the expressions to predict the MCF and SEA values of the structure are established. A layout strategy of the diaphragms for the TSTD as an energy-absorbing structure is summarized, which is beneficial for practical applications.